The Disease Burden in Fish Farm Management: An Integrative View and a Specific Vision in Europe - Francesc Padros; Hamish Rodger; Maria Constenla; Ana Herrero; Maurice Glucksman; Alberto Allepuz; Carlos Zarza (Reviews in Aquaculture, 2025)
In aquaculture, the interactions and balance—or imbalance—between the fish, the rearing environment, pathogens, and farm management determine the occurrence and impact of clinical diseases. The global assessment of the factors related to disease impact is commonly referred to as disease burden. This assessment goes beyond the economic consequences of mortality and morbidity, encompassing additional economic factors related to disease management, as well as broader social and political consequences. The concept of disease burden is gaining relevance in aquaculture, where disease poses serious threats to animal welfare, productivity, and economic sustainability. At the farm level, the consideration of fish as living assets includes aspects such as direct mortality, indirect effects of mortality, and morbidity. Furthermore, the impact of disease on key performance indicators, routine operations, and planned productivity are important consequences. Diseases on fish farms also require effective management, whether through the implementation of treatments or through preventive and biosecurity measures, both of which can have indirect impacts that must be properly analyzed. In many cases, the risks associated with disease necessitate appropriate surveillance by farms or regulatory authorities, and the cost of such surveillance and insurances should be considered part of the overall disease burden. Other important aspects such as the impact on animal welfare, wellbeing of farm staff, integration of the concept into certification schemes, and issues related to social perception, acceptance, and prestige are also examined. In addition, macroeconomic factors such as market impacts, governance, and a special emphasis on the One Health approach are addressed.